THE ROLE OF LEADERSHIP IN NATURAL RESOURCE CONSERVATION AND SUSTAINABLE DEVELOPMENT - A CASE STUDY OF LOCAL SELF-GOVERNMENT OF EASTERN SERBIA - Nebojša Marjanović; Violeta Jovanović; Tatjana Ratknić; Džejn Paunković (Ekonomika Poljoprivrede (1979), 2019)
Local authorities have a very important role in preserving natural resources and achieving the concept of sustainable development. Leadership, but primarily sustainable leadership, plays a major role in the management of natural resources. Sustainability at local level refers not only to environmental issues such as the conservation of natural resources, energy, and environment but also efforts to involve the community in the processes, develop organizational capacities and promote the principles of sustainable development. This research analyses the importance and role of the leadership of local self-government in the preservation of natural resources and the realization of the concept of sustainable development. The research was carried out in local governments on the territory of Eastern Serbia. The regression analysis was used to determine the interrelatedness between leadership and sustainable management of natural resources and practical application of the basic principles of sustainable development.